Allowable Span Length of Submerged Pipes Under the Effect of Hydrodynamic Forces - Ahmadian, Pakhshan; Turker, Umut (Elsevier Science Bv, 2016)
This study aims to calculate the maximum spanning lengths of different size High Density Polyethylene pipes (HDPE) at the intermediate zone of coastal environments. In order to do so, Reynolds number less than 3.5x105 and Keulegan Carpenter number between 4 and 7 at intermediate depth are accepted as the limitations of the work. The assigned limitations were useful to analyse the behaviour of submerged pipes in the absence of vortex induced vibration. Therefore, the velocity of sea current and the wave orbital velocity at intermediate depth are computed to determine the in-line and cross-flow net forces acting on spanning submerged pipes. Finally, comparing the yield stresses of pipes with the bending stresses due to external forces, the critical spanning length of high density polyethylene pipes are deduced. At constant diameter, the free spanning length of the pipes was increasing as the wall thickness of the pipes increases. The ratio of external forces to the weight of the pipe was not effective while deciding on the magnitude of spanning length of the pipes, which shows 0.5% changes while 30% changes occurred on the pipe diameter. (C) 2016 The Authors. Published by Elsevier Ltd.
World Multidisciplinary Civil Engineering-Architecture-Urban Planning Symposium (WMCAUS) -- JUN 13-17, 2016 -- Prague, CZECH REPUBLIC
Keywords: drag force; inertia force; lift force; span length